Validity of Problem-Based Learning Teaching Module to Improve Critical Thinking of High School Students on Atomic Structure Material - Saputri, Legendaria Raula; Wisudawati, Asih Widi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Chemistry learning, particularly in atomic structure, faces challenges due to its conceptual nature and difficulty in observation. Traditional teaching methods, which often render students passive, exacerbate this issue and hinder critical thinking skill development. To address this, a digital teaching module based on problem-based learning (PBL) was developed and designed for easy accessibility anytime and anywhere. This module promotes interactive learning centered on real-world problems, significantly enhancing students' critical thinking abilities. This study employs a research and development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The analyze stage involved observing the needs of high school chemistry teachers. The design stage included planning materials, creating the module design, and developing assessment instruments. The development stage involved quality evaluations by material experts, media experts, and high school chemistry teachers. Evaluation results showed highly positive feedback, with an ideal score of 93% from material experts, 91.67% from media experts, and an average score of 90.21% from five chemistry teachers, all classified as very good. The module is considered effective and offers an alternative approach to teaching atomic structure. Future studies are recommended to advance this module to the implementation phase, as this research has only reached the development stage.